2016
DOI: 10.31887/dcns.2016.18.4/jgoldstein
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress-immune programming of sex differences in comorbidity of depression and obesity/metabolic syndrome

Abstract: Major depressive disorder (MDD) is the number one cause of disability worldwide and is comorbid with many chronic diseases, including obesity/metabolic syndrome (MetS). Women have twice as much risk for MDD and comorbidity with obesity/MetS as men, although pathways for understanding this association remain unclear. On the basis of clinical and preclinical studies, we argue that prenatal maternal stress (ie, excess glucocorticoid expression and associated immune responses) that occurs during the sexual differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 159 publications
2
44
0
Order By: Relevance
“…The differences in future depression between metabolically healthy obesity men and women are still not known, but there are some studies on the different effects of sex of obesity and depression. One study proposed that prenatal stress-immune programming of the different sexes effects hypothalamic-pituitary-adrenal-gonadal axes and on metabolic and cardiac functions, leading to differences between the sexes in the comorbidity of major depressive disorders and obesity/metabolic syndrome [ 32 ]. Another study has shown that obesity has a relationship with different psychosocial profiles in both men and women [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in future depression between metabolically healthy obesity men and women are still not known, but there are some studies on the different effects of sex of obesity and depression. One study proposed that prenatal stress-immune programming of the different sexes effects hypothalamic-pituitary-adrenal-gonadal axes and on metabolic and cardiac functions, leading to differences between the sexes in the comorbidity of major depressive disorders and obesity/metabolic syndrome [ 32 ]. Another study has shown that obesity has a relationship with different psychosocial profiles in both men and women [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, data may differ depending upon sex, developmental stage investigated and whether total Bdnf gene expression or the levels of individual exons are measured (Boersma et al, 2014 ; Luoni et al, 2014 , 2016 ; Cirulli, 2017 ). Clinical and preclinical studies indicate that prenatal maternal stress that occurs during the sexual differentiation of the fetal brain has sex-dependent effects on brain development within highly sexually dimorphic regions that regulate mood, stress and metabolic function (Goldstein et al, 2016 ). Sex-dependent effects have been demonstrated in the response to stress, particularly in the case of prenatal stress as males with a history of in utero stress are more prone to develop anxiety-like behavior and cognitive alterations (Zuena et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to several lines of evidence, exposures to prenatal maternal stress occurring during the gestational period have sex-dependent effects on brain development within highly sexually dimorphic regions that are involved in the regulation of mood, stress responses, metabolic function, the autonomic nervous system, and the vasculature [ 5 ]. However, although the literature suggests that the sex-dependent impact of prenatal maternal stress is timing and brain region-specific, little is known about the mechanisms underlying these gender differences and the different vulnerability for the development of negative outcomes in male and female offspring.…”
Section: The Fetal Programming the Intrauterine Environment And The mentioning
confidence: 99%
“…The association between depression and obesity is very complex as they influence each other. Although a few studies have reported no significant associations between maternal overweight and/or obesity and depressive symptoms or vice versa [ 2 , 3 ], several lines of evidence have shown that among pregnant women, those with depression are more likely to develop obesity as compared with those nondepressed [ 4 , 5 ]. Similarly, it has also been demonstrated that pregnant obese women are more vulnerable to develop depressive symptoms during pregnancy and/or in the postpartum period than normal weight, pregnant women are [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%